IMPLEMENTATION OF SOCIALIZATION OF BANANA HEART EXTRACT AND PAPAYA LEAVES TO BREASTFEEDING MOTHERS AS AN EFFORT TO PROVIDE EXCLUSIVE BREASTFEEDING: local food as an effort to provide exclusive breastfeeding - Marniati M; Enda Silvia Putri; Sufyan Anwar; Itza Mulyani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Background: The living environment influences increasing the volume of breast milk in addition to family income and mother's knowledge. The problem in this study is the lack of volume of breast milk in breastfeeding mothers so it has a negative impact on the coverage of exclusive breastfeeding. The purpose of this study was to analyze the implementation of socialization of banana heart extract and papaya leaves on breastfeeding mothers as an effort to provide exclusive breastfeeding. This research method is an observational cross-sectional and pre-experimental design in the form of a one-group pre-post test design conducted in December 2021 in Aceh Barat with a sample of 45 mothers who have babies. The results of the study were based on before the implementation of the socialization test was carried out, the score was 17.8% for breastfeeding mothers, but after the implementation of the socialization test, the score was 48.9% for breastfeeding mothers. Where the mean value is 6.91 and the SD value is 1.345, while the P-value is 0.000 <α 0.05. Conclusion The changes that occurred to breastfeeding mothers were initially only 17.8%, but after socialization, it increased to 48.9% of mothers who breastfeed. If mothers regularly consume this extract from the beginning of pregnancy to breastfeeding, it is possible that all breastfeeding mothers will have their baby's needs met, so that the coverage of exclusive breastfeeding will be even better. Suggestions make it a habit for mothers to always breastfeed by regularly consuming foods that are high in nutritional value, such as extracts of Banana Heart and Papaya leaves which are easily available in the environment around the place of residence, from the beginning of pregnancy to the end of breastfeeding.